Implementation Of The Monte Carlo Method For Predicting New Student Enrollment At SMK Negeri 7 Bengkulu City - Fobi, Ahmad Julcer; Yupianti , Yupianti; Jumadi , Juju (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The purpose of this study is to apply the Monte Carlo method in predicting the number of new student enrollments at SMK Negeri 7 Bengkulu City. The very rapid development of technology and information in the current era provides many benefits that can help and facilitate human work, one of which is in the field of prediction. Techniques in making predictions or estimates are a very important medium in carrying out appropriate planning in the fields of business, education, economics and other fields with the aim of making decisions as a basis for strategies to improve the quality and quantity of an institution or organization, both private and government. SMK Negeri 7 Bengkulu City is one of the State Vocational High Schools in Bengkulu City, every year SMK N 7 Bengkulu City carries out the process of accepting new students. New Student Admissions (PPDB) is the initial process in teaching and learning activities. Currently, the problem that occurs in PPDB is the failure to achieve the quota of students who register, resulting in many empty seats. The research method used by the author is the system development method. The results of this study are that the application for predicting the number of new student enrollments using the Monte Carlo method has been successfully implemented and predicts the number of new student enrollments based on the chosen major. Second, to predict the number of new student registrations, a Monte Carlo prediction model was first created or formed. Third, by using this Monte Carlo method, SMK Negeri 7 Kota Bengkulu can evaluate and predict the number of new student registrations which can be used to make preparations such as classroom equipment, laboratory equipment, procurement of stationery and human resources (teachers and teaching staff).